1991
DOI: 10.1002/1097-0142(19910401)67:7<1921::aid-cncr2820670717>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric DNA index in the prognosis of colorectal cancer

Abstract: The authors investigated the relationship between flow cytometric DNA index (DI, defined as the ratio of the DNA content of malignant cells to that of normal cells) and other prognostic factors (grade and stage, anatomical site, age and sex) with the survival of 115 patients with colorectal cancer. Multiple biopsy specimens from 62 patients were taken during colonoscopy before surgery. Additional samples from 53 patients were obtained from paraffin-embedded material. All patients were treated with surgery only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
1
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 33 publications
3
27
1
1
Order By: Relevance
“…Several studies have reported the prognostic relevance of routine clinicopathologic features, whereas new parameters, like tumor DNA index and ploidy, vascular invasion, degree of necrosis, mucins, serotonin, and large bowel obstruction, have been proposed in predicting the overall survival for patients with CRC. [41][42][43] It can be speculated that the prognostic relevance of CATL, UPA, and PAI-1 in human carcinoma also may support a possible therapeutic approach in the future. Indeed, this can be obtained directly by inhibition of cathepsins 36 and UPA 44 or indirectly by inhibiting the binding of UPA to its receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the prognostic relevance of routine clinicopathologic features, whereas new parameters, like tumor DNA index and ploidy, vascular invasion, degree of necrosis, mucins, serotonin, and large bowel obstruction, have been proposed in predicting the overall survival for patients with CRC. [41][42][43] It can be speculated that the prognostic relevance of CATL, UPA, and PAI-1 in human carcinoma also may support a possible therapeutic approach in the future. Indeed, this can be obtained directly by inhibition of cathepsins 36 and UPA 44 or indirectly by inhibiting the binding of UPA to its receptor.…”
Section: Discussionmentioning
confidence: 99%
“…1b) differed significantly from that in the adenomas (Kolmogorovtases, higher than in adenomas overall, and comparable to DNA aneuploidy in the larger adenomas, lymph Smirnov test, P õ 0.001), and this is in agreement with results from cytogenetic and previous flow cytometric node metastases may have in part been generated early after the occurrence of infiltrative growth and studies. 20, 21 The incidence of DNA aneuploidy in primary colorectal carcinomas was significantly higher earlier than the generation of other metastases. This also applies to the difference in DNA aneuploidy incithan in adenomas (chi-square test, P Å 0.001) and / 7b52$$0976 03-12-97 09:27:31 canal W: Cancer dence between the lymph node metastases and the tases, and 25 % of the other hematogenous metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In cancers of the bladder (17), the ovary (18), and the colon (19), for example, it has been shown that aneuploid tumors are usually more aggressive than diploid tumors in terms of their clinical evolution. The reverse has been observed in the case ofcertain infant (20) and adult (21) brain tumors.…”
Section: Discussionmentioning
confidence: 99%